Treatment Patterns and Outcomes Among Patients With Advanced or Recurrent Endometrial Cancer Initiating First-Line Therapy in the United States - Robert L. Coleman; Jamie Garside; Jean Hurteau; Joehl Nguyen; Monica Kobayashi (Journal of Health Economics and Outcomes Research)
**Background:** Patients with advanced or recurrent endometrial cancer (EC) typically have limited treatment options and poor long-term survival outcomes following first-line therapy. Real-world treatment patterns and survival outcomes data are limited for patients in this setting.